2020
DOI: 10.6007/ijarbss/v10-i5/7248
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of Global Online Marketing Research Trends

Abstract: The revolution of the internet technology has increased the demand for online marketing strategies. Over the years, online marketing has received considerable attention owing to its advantages to both individuals and organizations. This study sought to analyze the global online marketing research trends from 1975 to 2019 through a bibliometric analysis procedure. A total of 789 published articles were retrieved from the Scopus database for the analysis. The results suggest that between 2001-2010, Google AdWord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
1
0
3
Order By: Relevance
“…With regard to research collaborations between countries, the USA and England were found to be the two most productive countries in terms of co-authored publications involving social capital (260 and 142 documents, respectively), as similarly revealed in previous studies (Garrigos-Simon et al. , 2018; Patrick and Hee, 2020). These two nations are in the center of Figure 8, in which the 38 countries that meet the threshold of five co-authored documents are shown (out of the total of 77 countries which have published on the topic of social capital).…”
Section: Resultssupporting
confidence: 80%
“…With regard to research collaborations between countries, the USA and England were found to be the two most productive countries in terms of co-authored publications involving social capital (260 and 142 documents, respectively), as similarly revealed in previous studies (Garrigos-Simon et al. , 2018; Patrick and Hee, 2020). These two nations are in the center of Figure 8, in which the 38 countries that meet the threshold of five co-authored documents are shown (out of the total of 77 countries which have published on the topic of social capital).…”
Section: Resultssupporting
confidence: 80%
“…Ozkose dan Gancer (2017) mendefinisikan analisis bibliometrik sebagai pendekatan dalam metode kuantitatif yang dapat menafsirkan pola publikasi melalui perhitungan statistika dan matematika (Demir et al, 2020). Pemilihan analisis bibliometrik karena pendekatan ini dapat digunakan untuk menganalisis tren global pada area atau topik tertentu yang diunggah pada jurnal akademik atau artikel (Patrick & Hee, 2020). Jurnal atau artikel akademik yang digunakan pada penelitian ini adalah jurnal atau artikel mengenai penelitian tanggung jawab sosial perusahaan pada bidang komunikasi dan kehumasan yang berasal dari pangkalan data ProQuest.…”
Section: Metode Penelitianunclassified
“…Studi analisis bibliometrik adalah pendekatan kuantitatif untuk menganalisis tren penelitian global di bidang atau topik tertentu berdasarkan jurnal atau artikel akademik yang diterbitkan (Patrick & Hee, 2020).…”
Section: Metode Penelitianunclassified
“…Studi pemetaan menggunakan analisis blibiometrik dengan topik tren global dalm riset pemasaran online yang telah dilakukan oleh Zurina Patrick dan Ong Choon Hee (Patrick & Hee, 2020). Studi tersebut meninjau 789 artikel penelitian yang diterbitkan dari tahun 1975 sampai 2019.…”
unclassified